Challenges Hindering Islamic Microfinance Banks’ Sustainable Financial Inclusion: A Case of Al-Hayat Microfinance Bank in Ogun State, Nigeria - Salaudeen, Adnan Opeyemi; Zakariyah, Habeebullah (El-Barka, 2022)
Microfinance is regarded as an effective technique of poverty alleviation since it provides access to financial resources that can assist in poverty reduction by increasing financial involvement and empowerment. However, despite the fact that microfinance banks account for the vast bulk of the market in Nigeria, with over 800, their contribution to the country’s economy is less than 1%. Additionally, the primary objective of poverty eradication has not been accomplished. Thus, existing research has positioned Islamic microfinance institutions as a viable tool for poverty alleviation in Nigeria. However, Islamic microfinance banks in Nigeria continue to witness minimal development. This research investigates the challenges hindering the development of Islamic microfinance banks in Nigeria. Semi-structured interviews were used to collect data for this study. In addition, data reduction, coding, integration, and visualisation steps are implemented to analyse data effectively. The finding shows that several regulatory issues, such as licence procedures requiring paid-up capital, are some challenges. Likewise, awareness, misconceptions, and acceptance remain significant hindrances faced by IMFBs in Nigeria. Additionally, IMFBs face some in-house challenges, such as a lack of Islamic fintech, convenient access to the unbanked community, and human capital. Consequently, the study recommends that stakeholders in the Nigerian financial system launch public awareness campaigns about the significance of Islamic microfinance banks in promoting financial inclusion and reducing poverty.